Seed Parameters and Germination of Gnetum ula Brongn.; An Endemic Gymnosperm from India - Ashwath, M. N.; Gurudev Singh, B.; Sathish, B. N.; Sheela, H. K.; Deepthi Dechamma, N. L.; Kushalappa, C. G. (Indian Forester, 2023)
No Abstract.